Strategi Komunikasi Politik pada Akun Instagram PKS Depok - Hari Rahman Hakim; Tariza Sudadih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the political communication strategy implemented by PKS Depok through their Instagram account. Discussing the importance of social media as a means of political communication in reaching potential voters. The research methodology in this study is qualitative with content analysis of PKS Depok's Instagram posts, focusing on the selection of orange, emphasizing the value of togetherness, and participation in social activities. The results of the discussion show PKS Depok's efforts in building a strong visual identity by using orange as the party's identity, as well as emphasizing togetherness and social activities as a way to build emotional attachment with voters. The implication is that this strategy can improve the party's image and community involvement through social media, but more attention is needed to diversify content in order to convey the party's programs and vision in more detail. This study uses a descriptive method with the aim of describing and identifying phenomena related to PKS Depok's social media posts systematically and objectively. A qualitative approach was chosen to collect and analyze data in depth, so that it can understand the experiences and perspectives of research subjects in a complex context. Data were collected through observations of PKS Depok's Instagram posts and literature studies related to the research theme. The author acts as a follower of the PKS Depok Instagram account, observes relevant posts, and analyzes data using qualitative techniques. The data findings are described and concluded as the final results of this study.